Constructed Masculinity in Jagdish Gimire’s Lilaam - Bista, Asmita (JODEM: Journal of Language and Literature, 2021)
This article focuses on gendered construction of masculinity in Jagdish Ghimire’s Lilaam. The main argument of this article is that masculinity is constructed entity; so, male characters of this novel constituted their masculinity through their performances. Moreover, the male characters of this novel confirm the socially accepted universal truths about being a woman or man; consequently, their exhibition of masculinity cause problems not only to them but also to the female characters. To support this argument, Connell’s and Kimmel’s idea of masculinity have been used as major theoretical parameters to analyze the text under scrutiny. They have claimed that conventional masculinity harms both women and men who are caught up in a systematic constructed limitation due to their prescribed gender roles. According to Connell, men are not born, they are made; in fact, men make themselves, actively constructing their masculinities within a social and historical context. Consequently, males undergo repression while exhibiting masculinity. The significance of this article is to analyze the condition of males residing in Manthali village that is situated on the bank of Tamakoshi river. The article concludes that the male characters of Lilaam cannot live happily and peacefully because snatching happiness and peace from their life, patriarchy buries them under the unbearable burden of masculinity.